A bibliometric analysis of research on the treatment of facial nerve palsy. Issue 33 (20th August 2021) - Goo, Bonhyuk; Kim, Ha-Na; Kim, Jung-Hyun; Nam, Sang-Soo
Abstract: Background: There are various treatments for facial nerve palsy, and research into this topic is ongoing. In the present study, we carried out bibliometric and visualized analyses to identify the trends of research into facial nerve palsy treatment. Methods: To identify articles, the SCOPUS database was searched for articles published from its inception to December 27, 2020. The search was conducted twice, with Search 1 investigating general treatment trends and Search 2 narrowing the scope to complementary and alternative treatment. The extracted keywords were analyzed using the Visualization Of Similarities (VOS) viewer. Through analysis of keywords, research hotspots in the treatment of facial nerve palsy were identified. Results: A total of 1609 and 223 articles were identified in Searches 1 and 2, respectively. The number of articles published each year showed a tendency to increase, and most of the studies were only conducted in a few countries. In terms of subject area, "medicine" was overwhelmingly the most common(77.6%). Based on the analysis of 316 keywords in Search1, "medication treatment, " and "complementary and alternative treatment" were the hotspots of research. Conclusion: This study provides the overall trends of facial nerve palsy treatment. To date, research on medication treatment has been main focus, and antiviral use among medication treatment and complementary and alternative treatment has emerged in recent years. Abstract : Supplemental Digital Content is available in the text